Utility of Real Time 3D Echocardiography for the Assessment of Left Ventricular Mass in Patients with Hypertrophic Cardiomyopathy: Comparison with Cardiac Magnetic Resonance. Issue 3 (3rd November 2015) - Avegliano, Gustavo P.; Costabel, Juan P.; Asch, Federico M.; Sciancalepore, Agustina; Kuschnir, Paola; Huguet, Marina; Tobon‐Gomez, Catalina; Frangi, Alejandro F.; Ronderos, Ricardo
Abstract : Introduction and objectives: Patients with hypertrophic cardiomyopathy (HCM) have irregular ventricular shapes with small and sometimes obliterated cavities at end‐systole that affect the quantification of left ventricular mass (LVM) by conventional methods, such as M‐mode or two‐dimensional echocardiography. The goal of this study was to validate the use of real time three‐dimensional echocardiography (RT3DE) to quantify LVM using cardiac magnetic resonance imaging (CMR) as a reference, in a large population of patients with different types of HCM. Methods: Forty‐eight consecutive patients with HCM had a complete transthoracic examination and CMR performed within 7 days. LVM was calculated by M‐mode and RT3DE and compared to CMR that served as gold standard. Results: Left ventricular mass calculated by RT3DE was 195 ± 41 g and 187 ± 49 g by CMR. The correlation between the two methods was moderate, with a Lin index of 0.63 and good linear correlation (r = 0.63, P < 0.0001). The correlation was high when RT3DE was of high or adequate image quality. The correlation between LVM by M‐mode and CMR was poor. Conclusion: Three‐dimensional echocardiography is an accurate method for the quantification of LVM in patients with different subtypes of HCM that is in better agreement with CMR reference values than M‐mode measurements.